Prosthetic rehabilitation of a severely resorbed mandibular ridge using the effective suction method - Novita Gabriela Andreas; Taufik Sumarsongko; Rasmi Rikmasari (Indonesian Journal of Prosthodontic, 2026)
Background: Mandibular ridge resorption commonly occurs after tooth loss and progressively reduces ridge height and contour, often resulting in a flat ridge. Severe resorption in edentulous patients creates challenges in complete denture fabrication, particularly in achieving adequate retention and stability. The mandibular suction effective denture technique was developed to improve retention by establishing a complete border seal and negative pressure beneath the denture base. Objectives: This case report aims to describe prosthetic rehabilitation of a patient with a flat mandibular ridge using the effective suction impression technique. Case Report: A 67-year-old female with complete edentulism and a flat mandibular ridge complained of difficulty in mastication and speech due to a loose, fractured denture. Rehabilitation was performed using the effective suction impression technique with a frame cut-back (FCB) tray and a closed-mouth impression method. Procedures included final impression making, jaw relation recording, artificial teeth arrangement, and insertion of complete dentures for both arches. Post-insertion evaluation showed good retention and stability, with improved comfort and masticatory function. Conclusion: The effective suction technique can provide improved retention, stability, and patient comfort in patients with flat mandibular ridges. Further clinical studies are needed to confirm its long-term success.